2001
DOI: 10.2170/jjphysiol.51.753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17.BETA.-Estradiol on Tension Responses and Fatigue in the Skeletal Twitch Muscle Fibers of Frog.

Abstract: Estrogens, like other steroid hormones, initiate their action via specific intracellular receptors [1]. The presence of estrogen receptors in the skeletal muscle cell was demonstrated in bovine [2], rabbit [3,4], and rat [5]. Skeletal myoblasts also expressed functional estrogen receptors [6]. The effects of estrogen on skeletal muscle contractility have been diversely reported. A long-term treatment of the developing rat with estrogen reduced the tetanus tension of skeletal muscle [7]. In women, the supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In contrast, our previous experiment in frog skeletal muscle revealed the presence of a much faster signaling initiated by the cell membrane ER, where administration of E2 quickly (in minutes) enhanced the twitch tension, presumably because of increased myoplasmic Ca 2? concentration [18]. These findings may suggest, as in other cell types, the presence of distinct nongenomic signalings linked to the cell membrane ERs, which operate in both fast and slow fashions via PLC-and MAPK-mediated pathways, respectively.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, our previous experiment in frog skeletal muscle revealed the presence of a much faster signaling initiated by the cell membrane ER, where administration of E2 quickly (in minutes) enhanced the twitch tension, presumably because of increased myoplasmic Ca 2? concentration [18]. These findings may suggest, as in other cell types, the presence of distinct nongenomic signalings linked to the cell membrane ERs, which operate in both fast and slow fashions via PLC-and MAPK-mediated pathways, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…Since we previously found rapid contractile effects of E2 on frog skeletal muscle [18], we were especially interested in the nongenomic actions of estrogen. For this purpose, we explored both total and nonnuclear expression of ER in relation to its biosynthesis and associated cellular signaling cascades in mouse C2C12 myoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was at least partly mediated via regulation of estrogen receptor alpha, both at transcript and protein level. Also Hatae 28 has shown an immediate increasing effect of estradiol administration on twitch force in frog skeletal muscle fibers.…”
Section: Discussionmentioning
confidence: 94%
“…Hatae 28 suggested that with high levels of E2 the reuptake of released Ca 2+ by sarcoplasmic reticulum could not be accomplished on time resulting in decreases in the following contraction. Thus, the same mechanism of E2 action that is involved in potentiating twitch may contribute to faster fatigability.…”
Section: Effect Of Hrt On Fatigabilitymentioning
confidence: 99%
“…Notably, acute 17β-estradiol treatment of in vitro frog skeletal muscle facilitated the fatigue response to repetitive tetanus stimuli with high frequency, and this direct and quick effect may be related to an increase in the imbalance of Ca 2+ turnover in the cytoplasm. 46 Estrogen also influences glucose uptake via regulation of GLUT4 expression in muscles. 47 GLUT4-deficient mice exhibit a hastened onset of muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%